O dragão da maldade contra o santo guerreiro (1969) e o terceiro cine: entre o cinema de autor europeu e o cinema clássico hollywoodiano - Castelo, Sander Cruz (2004)
The research seeks to delimit the constitution, in the late 60's of the last century, of the so-called third cine, third world aesthetic solution of the problems posed by classic Hollywood cinema and European author cinema.